Development of a Rapid in planta BioID System as a Probe for Plasma Membrane-Associated Immunity Proteins - Conlan, Brendon; Stoll, Thomas; Gorman, Jeffrey J.; Saur, Isabel; Rathjen, John P. (Frontiers in Plant Science, 2018)
Plant pathogens secrete effector molecules that suppress the plant immune response to facilitate disease development. AvrPto is a well-studied effector from the phytopathogenic bacterium Pseudomonas syringae. Here we utilise an in planta proximity dependent biotin ligase labelling technique (BioID) in combination with AvrPto to identify proximal proteins that are potential immune system components. The labelling technique biotinylated proteins proximal to AvrPto at the plasma-membrane allowing their isolation and identification by mass spectrometry. Five AvrPto proximal plant proteins (APPs) were identified and their effect on plant immune function and growth was examined in Nicotiana benthamiana leaves. One protein identified, RIN4, is a central immune component previously shown to interact with AvrPto. Two other proteins were identified which form a complex and when silenced significantly reduced Pseudomonas syringe tabaci growth. The first was a receptor like protein kinase (APK1) which was required for Pto/Prf signalling and the second was Target of Myb1 (TOM1), a membrane associated protein with a phosphatidylinositol 5-phosphate (PtdIns5P) binding motif. We have developed a technology to rapidly determine protein interactions within living plant tissue. It is particularly useful for identifying plant immune system components by defining pathogenic effector protein interactions within their plant hosts.